A case of acute and late coronary events after blunt chest trauma: Attention to the late onset angina. Issue 4 (April 2018) - Watari, Yuichiro; Ueda, Hironori; Miyamoto, Shogo; Hashimoto, Yu; Tomimoto, Hideko; Watanabe, Yoshikazu; Urabe, Yoji; Yamazato, Ryo; Mitsuba, Naoya; Miura, Fumiharu; Takahashi, Masashi; Okamoto, Mitsunori
Abstract: Mechanisms of acute myocardial infarction caused by traumatic coronary artery injury have been reported. However, late-onset coronary artery stenosis associated with trauma is less well known. We experienced a case in which acute myocardial infarction of the right coronary artery occurred at the time of blunt chest trauma (BCT) caused by a traffic accident and an increase in coronary artery stenosis in the left anterior descending artery (LAD) branch about 1 year later. A comparison of a volume-rendering image created from enhanced-contrast computed tomography at the time of trauma and coronary angiography revealed that the trauma site and the stenotic lesion in the LAD were in very close proximity, suggesting to us that traumatic coronary artery injury without flow limitation may have developed into high-grade stenosis in the LAD 1 year later. In this case we were able to demonstrate a causal relationship between BCT and delayed coronary artery stenosis. After BCT, it is necessary to be aware of the possibility of delayed coronary artery stenosis even if coronary injury is absent in the acute phase. <Learning objective: Careful follow up for the onset of angina pectoris is necessary to prevent coronary events after blunt chest trauma.>